2011
DOI: 10.1021/nn2016666
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrolysis of Ammonia Borane via Cobalt Palladium Nanoparticles

Abstract: Monodisperse 8 nm CoPd nanoparticles (NPs) with controlled compositions were synthesized by the reduction of cobalt acetylacetonate and palladium bromide in the presence of oleylamine and trioctylphosphine. These NPs were active catalysts for hydrogen generation from the hydrolysis of ammonia borane (AB), and their activities were composition dependent. Among the 8 nm CoPd catalysts tested for the hydrolysis of AB, the Co(35)Pd(65) NPs exhibited the highest catalytic activity and durability. Their hydrolysis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
145
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(156 citation statements)
references
References 40 publications
10
145
0
1
Order By: Relevance
“…However, more economical, yet more active Pd catalysts might be developed by preparing bimetallic Pd alloy nanoparticles in the presence of a first-row transition metal (Fe, Co, Ni, Cu). In this respect, we have recently reported that carbon supported CoPd [12] and reduced graphene oxide (RGO) supported NiPd [13] alloy NPs were highly active catalysts in the hydrolysis of AB. On the other hand, limited number of Cubased catalysts has been reported for the hydrolysis of AB as seen from Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, more economical, yet more active Pd catalysts might be developed by preparing bimetallic Pd alloy nanoparticles in the presence of a first-row transition metal (Fe, Co, Ni, Cu). In this respect, we have recently reported that carbon supported CoPd [12] and reduced graphene oxide (RGO) supported NiPd [13] alloy NPs were highly active catalysts in the hydrolysis of AB. On the other hand, limited number of Cubased catalysts has been reported for the hydrolysis of AB as seen from Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…So far, numerous monometallic catalysts, such as noble metals Rh [10e12], Pd [10,13], Ru [10,13e17] and Pt [10] and non-noble metals Fe [18,19], Ni [17,18,20,21], Co [11,18,21] have been evaluated. Besides monometallic catalysts, bimetallic ones, such as core/shell structured Ni 1Àx @Pt x [22] and Ni@Ru [23] nanoparticles and alloyed RuNi [17], CoPt [24], RuCo and RuCu nanoparticles [25], and trimetallic ones, such as CoeNieP [26] and Cu@FeNi [27], were also tested for AB hydrolysis. Ru nanoparticles have been identified as one of the most effective ones.…”
Section: Introductionmentioning
confidence: 99%
“…To be active in the hydrolysis of AB, catalysts are required to have small size (<10 nm), which causes an increase in the surface area and thus the number of active sites [24]. For this purpose, ligands are often used to control the size of catalysts and prevent their agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…11,13,14 The enhancement of the catalytic activity of the supported noble metal can be attained by different routes; i) increasing the metal dispersion on the support by the synthesis of very small NPs, 15 ii) alloying the noble metal with a transition metal, (which is also attractive due to the cost reduction of the catalysts) 11,16,17 and iii) supporting the NPs on an UV-Vis active support to upgrade the electron-transfer from the support to the NPs. 1, 18 In the present study, the synthesis of Pd and Co-Pd…”
mentioning
confidence: 99%